Wage subsidies to combat unemployment and poverty: Assessing South Africa's options - Burns, Justine; Edwards, Lawrence; Pauw, Karl (International Food Policy Research Institute, 2010)
Wage or employment subsidies have been used in both developed and developing countries to raise employment levels. Various advisers to the South African government have endorsed wage subsidies as a policy measure to deal with this country's massive unemployment problem. This paper takes stock of the international literature and conducts an economywide macro-micro analysis to obtain insights into wage subsidy design and implementation issues facing developing countries. It also investigates whether this policy measure is appropriate in dealing with South Africa's particular sources of unemployment. We argue that although wage subsidies may be successful at creating jobs in South Africa, they should not be seen as the primary or dominant policy instrument for dealing with the broader unemployment problem. To enhance the effectiveness of wage subsidies, they should preferably be linked to structured workplace training, be targeted to industries where employment will be responsive to changes in labor costs, and be focused on the youth. In the long run, addressing unemployment in South Africa requires policies that improve economic growth and the economy's employment absorption capacity, that raise skills of new labor market entrants, that reduce labor market rigidities, and that promote effective job search, especially among the youth.